Forceps minor damage and co-occurrence of depression and fatigue in multiple sclerosis. (October 2014) - Gobbi, C; Rocca, MA; Pagani, E; Riccitelli, GC; Pravatà, E; Radaelli, M; Martinelli-Boneschi, F; Falini, A; Copetti, M; Comi, G; Filippi, M
Objective: Using diffusion tensor magnetic resonance imaging (DT MRI), we analyzed the architectural integrity of the brain white matter (WM) from a large cohort of MS patients to identify the structural substrates of the concomitant presence of depression and fatigue. Methods: Brain dual-echo, 3D T1-weighted and DT MRI scans were acquired from 147 MS patients and 90 gender- and age-matched healthy controls (HCs). Patients were stratified by the presence of depression (92 depressed (D), 55 not depressed (nD)) and fatigue (81 fatigued (F), 66 not fatigued (nF)). Sixty-five patients had co-occurrence of depression and fatigue (DF). Whole-brain voxel-wise comparisons of WM DT MRI abnormalities were performed using tract-based-spatial-statistics (TBSS). Tract-specific analyses were run in brain WM tracts using standard-space templates. Results: Whole-brain voxel-wise analysis yielded no significant differences between patient subgroups. At tract-specific analysis, DF patients had reduced fractional anisotropy (FA) of the forceps minor. Reduced FA of the right anterior thalamic radiation and right uncinate fasciculus was found in F-MS vs not F-MS patients after correcting for depression. No significant differences were found between D vs not D-MS patients, after correcting for fatigue. Conclusions: This study provides evidence for partially overlapping damage to frontal and fronto-temporal pathways underlying depression and fatigue in MS.